Use of administrative record linkage to examine patterns of universal early childhood health and education service use from birth to Kindergarten (age four years) and developmental vulnerability in the Preparatory Year (age five years) in Tasmania, Australia. Issue Volume 6:Number 3(2021)Special Issue (2021) - Taylor, Catherine L.; Christensen, Daniel; Venn, Alison J.; Preen, David B.; Stafford, Joel; Hansen, Emily; Jose, Kim; Zubrick, Stephen R.
No abstract available